Farmers' attitudes towards risk and their willingness to pay for crop insurance in Ketara, Terengganu, Malaysia - Roslan, Nurul Asrin (2013)
Paddy or rice industry is as important as other agricultural industry in the effort to attain the food security goals. Despite heavy intervention by the government, paddy production undoubtedly faces numerous risks include weather, the exposure of farmers to risky events such as drought, pest and disease. Exploring attitude of farmers toward risk is important in understanding their managerial decisions. The objectives of this study are to (1)To determine the level of risk attitudes of the paddy farmers; (2)To investigate the relationship between risk attitude and factors that influence farmer’s attitude according to their socio-economic profiles, and (3)To estimate the insurance premiums farmers are willing to pay (WTP) for crop insurance in IADA Ketara. The analysis shows that average age of paddy farmers was 48 years old, had six dependents including farmer himself. The average years of paddy farming experience was about 20 years. An average farm size was 3.34 hectares with the average net income per season was RM 15, 872.20. The sample average score for risk attitude was 3.10 indicate the farmers are willing to accept a little more risk than a risk neutral person. Reliability analysis indicates which statements contribute in explaining the risk attitudes. A set of 47-statements on how farmers are managing risks was analyzed. A set of 24-statements scale which offered the best explanation of the variance with the overall coefficient alpha of 0.728. This indicated the communal variation of 73% is caused by risk attitudes. The refined 24-statements scale developed was used to determine the risk attitudes of paddy farmers in Ketara. The 24-items attitudinal score revealed farmers in Ketara were slightly risk seekers than risk neutral persons, the sample average score for risk attitude statements was 3.49. This exploratory factor analysis used to identify the loading factors does not show a clear effect of more than one underlying construct best represents the factor. The analysis indicated eight-factor solution was factors that have eigenvalues over 1. Kaiser-Meyer-Olkin (KMO) value was 0.666 with the range of communalities from 0.458 to 0.722. Varimax- rotated component analysis factor matrix illustrating the factor loading range of 0.417 to 0.783. The factors affecting the risk attitudes of paddy farmers were analyzed using regression analysis. Four variables- age, level of education, number of times attended seminars/courses and paddy planting as main occupation significant in determining the risk attitudes. The contingent valuation method analysis found the percentage of a “Yes” response increasing as the bid amount decreases. Logistic regression analysis identified four factors- age, gross income, subsidy and bid price significantly related to the farmers’ willingness to pay for crop insurance. The mean willingness to pay (WTP) for crop insurance is found to be RM 56 per season, equivalent to 5.6% of RM 1000 sum insured or coverage. Finding of risk attitudes suggests that Malaysia’s government should focus on developing farm policies that help farmers reduce risk. The feasibility of crop insurance is currently being investigated. Attitude toward risk is an important factor influencing farmer’s demand for crop insurance.